2012
DOI: 10.4314/ajtcam.v9i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Traditional Medicine Utilization among Persons Living With AIDS (PLWA) on Antiretroviral (ARV) and Prophylaxis Treatment in both Rural and Urban Areas in South Africa

Abstract: Previous studies have reported that majority of antiretroviral (ARV) treatment-naïve patients use traditional medicine (TM). Given that TM use is ubiquitous in South Africa especially for chronic conditions, there is a potential for ARV non-adherence and serious drug interactions among patients with HIV/AIDs who use TM. The motivating factors for TM use in HIV/AIDS patients on ARV and prophylaxis treatment have not been well defined in South Africa. This study aimed to investigate the prevalence, facilitators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 16 publications
5
32
1
Order By: Relevance
“…There was no statistically significant association between sociodemographic characteristics (gender, age, employment status and level of education) and the use of herbs. Similar results were obtained where it was reported that having a rural dwelling, female gender, older age, a lack of formal education, not being married, having employment and haven been HIV positive for less than 5 years were all predictors of traditional medicine use amongst people living wit h AIDS (Oreagba et al, 2011;Hughes et al, 2012).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…There was no statistically significant association between sociodemographic characteristics (gender, age, employment status and level of education) and the use of herbs. Similar results were obtained where it was reported that having a rural dwelling, female gender, older age, a lack of formal education, not being married, having employment and haven been HIV positive for less than 5 years were all predictors of traditional medicine use amongst people living wit h AIDS (Oreagba et al, 2011;Hughes et al, 2012).…”
Section: Resultssupporting
confidence: 83%
“…This finding compares favorably with earlier studies (Oreagba et al, 2011;Hughes et al, 2012). This is probably due to the belief of these individuals that the different constituents in the "agbo" are able to bring them speedy healing.…”
Section: Resultssupporting
confidence: 81%
“…Previous studies elsewhere have indicated a need for improved care for People living with HIV (PLwHIV), with reports indicating emergence of resistant HIV strains [5], unsustainable donor driven free public sector provision of Antiretroviral treatments (ART), inhibited access to treatment due to factors such as lack of confidentiality, lack of transport to hospitals, shortage of health workers, long queues, and lack of adherence due to adverse drug reactions [6,7]. Some HIV patients resort to use of ethnomedicinal plants as an alternative or concomitant use with ARTs in an attempt to overcome these challenges [8].…”
Section: Introduction and Background Informationmentioning
confidence: 99%
“…For instance, HSV has been shown to respond very well to plant species such as Euphorbia continifolia, Euphorbia tirucali [10] and Carrisa edulis [11]. However, the health value of the majority of the medicines are still mainly anecdotal and the utilization seem to be increasing and dynamic, fueled by problems of HIV and other chronic conditions [6,8].…”
Section: Introduction and Background Informationmentioning
confidence: 99%
“…A 2012 cross-sectional study which involved 100 participants enrolled at ARV clinics in two South African provinces showed that less than 20% of participants used TM and ARV simultaneously 11 . However, close to 80% of participants utilised TM before contracting HIV, which is in keeping with approximate estimates by the WHO 12 .…”
Section: Introductionmentioning
confidence: 99%